CE: Original Research. Issue 3 (March 2019) - Steis, Melinda R.; Unruh, Lynn; Gurupur, Varadraj Prabhu; Shettian, Emilia; Rowe, Meredeth; Golden, Adam
Abstract : N/A: Background: When older adults with cognitive impairment develop new physical or behavioral symptoms, their family caregivers face a difficult decision: whether and when to seek professional medical care. Most family caregivers lack formal training in assessment and may have difficulty making such decisions. The Veterans Health Administration's home-based primary care (HBPC) program, which is widely available, offers community-dwelling frail veterans and their family caregivers guidance, with the goal of reducing hospitalization and institutionalization in long-term care facilities. Objective: This study sought to assess the frequency with which family caregivers of cognitively impaired older adults sought prehospital guidance from health care professionals when that resource was available to them, and to describe the characteristics of such events. Methods: This study used a retrospective chart review of patients who were enrolled in the Orlando Veterans Affairs Medical Center HBPC program for at least one month between October 1, 2013, and September 30, 2014; had a diagnosis indicative of cognitive impairment (Alzheimer's disease, vascular dementia, or mild cognitive impairment); had a dedicated family caregiver; and were not enrolled in hospice care. Data were collected from data collection templates and nurses' narrative notes. Univariate descriptive analyses were conducted regarding the type of staff contacted by family caregivers, the presenting diagnoses, the guidance offered by staff, and the number of unplanned acute care encounters. Results: Among the 215 patients studied, there were 254 unplanned acute care encounters (including ED visits followed by discharge to home and ED visits resulting in hospital admission). Family caregivers sought guidance from a health care professional 22% of the time before such an encounter. The presenting clinical issues were most often new problems (43%) that included falls, feeding tube problems, fever, new pain, rash or other skin problems, and unexplained edema. Overall, 25% of all unplanned acute care encounters were for reasons considered potentially avoidable. About half of the patients who were subsequently hospitalized had symptoms of delirium, indicating that their illness had significantly advanced before presentation. Conclusions: It's important for health care professionals to ensure that family caregivers of cognitively impaired older adults can access professional guidance readily when facing decisions about a loved one's care, especially when there is an acute onset of new symptoms. Teaching caregivers how to recognize such symptoms early in order to prevent exacerbations of chronic illness and subsequent hospitalization should be a high priority. Our findings underscore the need to do so, so that caregivers can best use the resources that HBPC programs have (or ought to have) in place, in particular 24/7 guidance and decision assistance. Abstract : The authors assessed the frequency with which family caregivers of older veterans with cognitive impairment sought guidance for new physical or behavioral symptoms and described the characteristics of such events, including the diagnoses and advice given.